Including values of citizenship into the elementary schools curriculum - Malihe Ashtiani; Kourosh FathiVājargāh; Mohammad YamaniDuziSorkhabi (فصلنامه نوآوری‌های آموزشی, 2006)
In the last few decades teaching values of citizenship has become an international mental concern and has formed a new view in education. An interest in teaching values of citizenship in commensurate with the culture and beliefs specific to each society has been established due to the need of training responsible and knowledgeable persons and also because of a continuous increase in communication, emergence of different cultures, and presentation of a variety of citizenship patterns, which in case of not being relevant  to the national culture, they will damage the concept and act of responsible and active citizenship. In this scenario, finding an identity and coexistence on an international scale is sometimes difficult for the adolescent.